2015
DOI: 10.1007/s10853-015-9428-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of barium boron aluminosilicate glass sealants using a sol–gel route for solid oxide fuel cell applications

Abstract: Development of barium boron aluminosilicate glass sealants using a sol-gel route for solid oxide fuel cell applications. (2016) Journal of Materials Science, 51 (2). 979-988.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Four glass-ceramic sealants, with a T g between 596 and 626 °C, showed adequate electrical insulation after a sealing procedure and stable CTE and microstructure after sealing and ageing operation (800 °C-100 h) in air atmosphere. Furthermore, any reaction product at the steel interconnector-glass interface was observed and no hexacelsian or monocelsian crystals were identified in the formed glass-ceramic seals [24]. However, only the CM2 glass (chemical composition: 36%BaO-2.6%Al 2 O 3 -10.3%B 2 O 3 -10.3%MgO-10.3% CaO-30.7%SiO 2 ) allowed preserving the gas-tightness of steel-glasssteel assemblies thermally treated at 700 °C or at 800 °C during 1000 h in air and in H 2 /H 2 O atmospheres [25,26].…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…Four glass-ceramic sealants, with a T g between 596 and 626 °C, showed adequate electrical insulation after a sealing procedure and stable CTE and microstructure after sealing and ageing operation (800 °C-100 h) in air atmosphere. Furthermore, any reaction product at the steel interconnector-glass interface was observed and no hexacelsian or monocelsian crystals were identified in the formed glass-ceramic seals [24]. However, only the CM2 glass (chemical composition: 36%BaO-2.6%Al 2 O 3 -10.3%B 2 O 3 -10.3%MgO-10.3% CaO-30.7%SiO 2 ) allowed preserving the gas-tightness of steel-glasssteel assemblies thermally treated at 700 °C or at 800 °C during 1000 h in air and in H 2 /H 2 O atmospheres [25,26].…”
Section: Resultsmentioning
confidence: 94%
“…However, promising performances had been obtained on short-term or on mid-term operations in air (up to 1500 h in dual atmosphere with no delamination [19]), in dual atmosphere (no delamination after 750 h [20]) or in real testing conditions with thermal cycles for SOFC applications [21]. In our previous works, we had developed a new sol-gel route to synthesize barium (boron) aluminosilicate glass sealants in order to process these glasses at a lower temperature than using a solid-state route and to improve the performance of these glasses for SOFC applications [22][23][24][25][26]. Indeed, many studies showed that the use of gel mixture could decrease the temperature of glass formation until 200 K below (possibly more) those required when using conventional batch material [27][28][29].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations